DEVELOPMENT OF THE SELECTIVE NUTRIENT MEDIUM FOR ISOLATION OF TOXIN PRODUCING STRAINS OF C. DIFFICILE (World Science, 2020)
Enterocolitis disorders caused by Clostridioides difficile infection still remain a serious health problem in the world. In many countries CDI is officially considered a nosocomial infection that causes considerable economic losses, including diagnostic and treatment costs. According to the existing data, C. difficile is the main agent causing antibiotic – associated diarrhea and the main etiologic factor of the pseudomembranous colitis (PMC) that often develops in case of complete destruction of the intestinal flora due to the use of antibiotics or chemotherapeutic agents. There is no official registration of CDI in Ukraine, therefore the official incidence and lethality rates are absent. At this time, the problems of development and improvement of selective nutrient mediums and quick, affordable bacteriological methods of C. difficile isolation are especially relevant.The comparative study of the efficacy of the known commercial nutrient mediums for isolation of toxin-producing strains of C. difficile was carried out and composition of a new, original selective nutrient medium was proposed. Unlike existing analogs, the proposed nutrient medium is suitable for the simultaneous isolation of the agent from the clinical material and detection of toxin-producing properties due to its high growth properties, optimal transparency and density.